Recurrent respiratory papillomatosis with pulmonary cystic disease in a child, following maternal genital warts. Issue 1 (February 1997) - Sadikot, R T; Andrew, A C; Wilson, J D; Arnold, A G
Abstract : Human papillomavirus (HPV) infection of the genital tract is associated with the development of genital warts. A causal link between maternal HPV infection and development of laryngeal papillomatosis in the offspring has been proposed. We report a case of pulmonary cystic disease, a rare but serious complication of laryngeal papillomatosis in a child, following maternal genital warts.